Study on the influence of sliding bearing stiffness on the dynamic response of hydro-generator shaft - Ri, Yongjae; Ryang, Sunghyon; Ryong, Gukhyon (Zielona Góra: Uniwersytet Zielonogórski)
The dynamic modeling of the main shaft system of a hydro turbine generator is carried out by considering the combined effects of unbalanced mass force, magnetic pull force, hydrodynamic force and oil film force of the sliding bearing, its critical rotational speed is obtained, the effect of the sliding bearing stiffness at each journal on the critical rotational speed of the whole shaft system is evaluated, and the method is proposed to improve the stability of the hydro turbine generator by changing it, and the validity is demonstrated by the field test results.
Keywords: hydro-turbine generator; dynamic modeling; critical rotational speed; sliding bearing stiffness